Evaluation of the Antioxidant Properties and Biological Effects of a Novel Combined Barberry Root–Propolis Extract on HEK293T Cells - Dana Marcinčáková; Nikola Hudáková; Michal Miłek; Mária Kolesárová; Małgorzata Dżugan; Dasa Cizkova; Jaroslav Legáth (Pharmaceuticals)
Background/Objectives: The health benefits of honeybee products and herbs are well known, and their appropriate combination may enhance their biological efficacy. This study investigated the biological properties of a combined barberry root and propolis extract (PBE) in comparison to a propolis extract (PE), a barberry root extract (BE), and pure berberine (BN). Methods: The antioxidant properties were evaluated using DPPH and FRAP methods and total phenolic contents (TPC) were assessed by the Folin–Ciocalteu method. HPTLC was used to quantify the BE in the tested samples. Their effect on HEK293T cells was monitored in real-time by using the xCELLigence system which recorded changes in the proliferative activity (PA). The metabolic activity (MA) was evaluated using an MTS test and cell migration was analyzed via a scratch assay. Results: The PE exhibited a higher TPC (198.67 mg/g) than the BE (119.3 mg/g). The PBE exhibited a comparable antioxidant effect to that of the PE. In the cell assays, the PE, the BE, and BN significantly reduced the proliferative activity at higher concentrations (p < 0.0001) while the PBE demonstrated a lower cytotoxicity and proved to be safer for the tested cells. The highest IC50 value was determined for the PBE (130 µg/mL), suggesting that this combination has a reduced cytotoxicity. However, the scratch test did not confirm a significant supportive effect of the PBE on cell migration. Conclusions: Although the PBE did not show enhanced antioxidant properties, it may mitigate cytotoxicity and support proliferation at lower concentrations. This suggests that extraction of raw propolis with a previously prepared barberry extract results in a safer preparation, but its therapeutic potential requires further studies using biological models.